Heritability and genetics correlations for body weight in escargots - Felipe André Oliveira Freitas; Eula Regina Carrara; Giovanni Ladeira; Matheus Lourenço; Thamires Leôncio; Claudiana Miranda; Fernanda Larissa César; Leila de Genova Gaya (Acta Scientiarum. Animal Sciences, 2022)
The objective of this study was to estimate genetic parameters for body weight at 60 (P60), 90 (P90), and 120 (P120) days of age in escargots of the subspecies Cornu aspersum maximum, evaluating the influence of fixed and covariable effects on these traits. The data used were collected from escargots kept in a total confinement system. The significant fixed effects and covariates for these traits were tested in a general linear model by the F-test, considering a level of significance of 5%. Both the fixed effects of box and birth year and the quadratic effect of age of weighing as a covariate were significant (p < 0.05) for P60, P90, and P120. The Restricted Maximum Likelihood (REML) methodology was used to estimate (co)variance components and genetic parameters. High heritability for P60, P90, and P120 (0.38, 0.55 and 0.78, respectively) and high genetic correlations (0.58 to 0.77) among the traits were observed. The genetic parameters can be used as a basis for studies and practical applications to increase zootechnical indexes in this population.